Das Hypopygium von Dolichopus Latreille unter besonderer Berücksichtigung der Muskulatur und der Torsion (Diptera: Dolichopodidae). - Bährmann, Rudolf (Contributions to Entomology = Beiträge zur Entomologie, 1966)
A study was made of the musculature and the resulting mobility of the hypopygium in the genus Dolichopus Latreille. A possible homology in the musculature of the hypopygium of the genera Dolichopus and Emjris (Empididae) is pointed out. It appears from an investigation of the positions of intestine and vas deferens in the genus Dolichopus that this genus has forms without circumvolution of the intestine by the vas deferens as well as forms in which this circumvolution is almost complete. The irregularity of torsion, which occurs already in the Dolichopodinae, is evidence against the assumption of a synapomorphy between Dolichopodidae and Cyclorrhapha.